Phytochemicals, Nutritional Value, Antioxidant, and Anticoagulant Activity of Lactuca sativa L. Leaves and Stems - Hanin Nafed Mughrbi; Abdurazag Abdussalam Auzi; Hamza Maghrbi (Borneo Journal of Pharmacy, 2020)
The main ingredient in the daily salad dish is the leaves of Lactuca sativa, while the stems are usually discarded and not eaten. This study was conducted to compare the stems and leaves of two selected L. sativa varieties (L. sativa var. longifolia L. and L. sativa var. capitata L.) related to the preliminary phytochemical investigation, nutrient content, DPPH assay, and in vitro anticoagulant activity by determination of prothrombin time (PT) and activated partial thromboplastin time (aPTT). The findings revealed almost the same phytoconstituents in the leaves and stems of each variety, such as terpenoids, flavonoids, coumarins, and others. Exceptionally, tannins have only been detected in the leaves. Compared to the stems, the leaves of both varieties showed statistically significantly higher levels of raw protein and raw fat. For the DPPH assay, the leaves of both varieties have a statistically significantly higher antioxidant activity than the stems. The leaves and stem extract of the two selected varieties showed a significant prolongation of PT (P <0.05 vs. NS= 12:30 s). On the other hand, the aPTT test showed a significant increase in aPTT (P <0.05 vs. NS = 32:44 s) in the stem extract of both varieties, whereas there was no statistically significant increase in aPTT in the leaves of both varieties. Both parts of each variety have a diversity of phytochemicals and nutrients. The leaves of both varieties have a higher antioxidant activity than the stems. While the stems had higher anticoagulant activity than the leaves.